Active and Accurate trans-Translation Requires Distinct Determinants in the C-terminal Tail of SmpB Protein and the mRNA-like Domain of Transfer Messenger RNA (tmRNA) - Camenares, Devin (American Society for Biochemistry and Molecular Biology, 2013)
Unproductive ribosome stalling in eubacteria is resolved by the actions of SmpB protein and transfer messenger (tm) RNA. We examined the functional significance of conserved regions of SmpB and tmRNA to the trans-translation process. Our investigations reveal that the N-terminal 20 residues of SmpB, which are located near the ribosomal decoding center, are dispensable for all known SmpB activities. In contrast, a set of conserved residues that reside at the junction between the tmRNA-binding core and the C-terminal tail of SmpB play an important role in tmRNA accommodation. Our data suggest that the highly conserved glycine 132 acts as a flexible hinge that enables movement of the C-terminal tail, thus permitting proper positioning and establishment of the tmRNA open reading frame (ORF) as the surrogate template. To gain further insights into the function of the SmpB C-terminal tail, we examined the tagging activity of hybrid variants of tmRNA and the SmpB protein, in which the tmRNA ORF or the SmpB C-terminal tail was substituted with the equivalent but highly divergent sequences from Francisella tularensis. We observed that the hybrid tmRNA was active but resulted in less accurate selection of the resume codon. Cognate hybrid SmpB was necessary to restore activity. Furthermore, accurate tagging was observed when the identity of the resume codon was reverted from GGC to GCA. Taken together, these data suggest that the engagement of the tmRNA ORF and the selection of the correct translation resumption point are distinct activities that are influenced by independent tmRNA and SmpB determinants.